A scoping review of Augmentative and Alternative Communication (AAC) interventions in Low-and Middle-Income Countries (LMICs). (3rd April 2022) - Muttiah, Nimisha; Gormley, Jessica; Drager, Kathryn D. R.
Abstract: Currently, a small number of studies discuss augmentative and alternative (AAC) interventions in low- and middle-income countries (LMICs). The primary purpose of this scoping review was to summarize the current evidence base on communication-based interventions and partner training in LMICs, to explore and identify gaps in the AAC evidence base and guide future research. A total of 18 studies were identified. The results revealed many positive outcomes arising from AAC interventions, including increased communication, improved participation, increased knowledge about communication, and increased use of partner communication strategies, thus adding to the evidence base that AAC can be successfully implemented in LMICs. However, these studies did not broadly represent most LMICs and there were only a handful of indirect intervention studies training communication partners. To this end, there is an urgent need to expand the level of AAC intervention research conducted in LMICs in order to better serve individuals with complex communication needs living in these countries.